Capacitive Control of Spontaneously Induced Electrical Charge of Droplet by Electric Field-Assisted Pipetting - Lee, Horim; Choi, Dongwhi; Kim, Dong Sung; Lim, Geunbae (Nano-Micro Letters, 2015)
The spontaneously generated electrical charge of a droplet dispensed from conventional pipetting is undesirable and unpredictable for most experiments that use pipetting. Hence, a method for controlling and removing the electrical charge needs to be developed. In this study, by using the electrode-deposited pipet tip (E-pipet tip), the charge-controlling system is newly developed and the electrical charge of a droplet is precisely controlled. The effect of electrolyte concentration and volume of the transferred solution to the electrical charge of a dispensed droplet is theoretically and experimentally investigated by using the equivalent capacitor model. Furthermore, a proof-of-concept example of the self-alignment and self-assembly of sequentially dispensed multiple droplets is demonstrated as one of the potential applications. Given that the electrical charge of the various aqueous droplets can be precisely and simply controlled, the fabricated E-pipet tip can be broadly utilized not only as a general charge-controlling platform of aqueous droplets but also as a powerful tool to explore fundamental scientific research regarding electrical charge of a droplet, such as the surface oscillation and evaporation of charged droplets.